Improving the catalytic activity for hydrogen evolution of monolayered SnSe2(1−x)S2x by mechanical strain - Dong, Sha; Wang, Zhiguo (Beilstein Journal of Nanotechnology, 2018)
Exploring efficient electrocatalysts for hydrogen production with non-noble metals and earth-abundant elements is a promising pathway for achieving practical electrochemical water splitting. In this work, the electronic properties and catalytic activity of monolayer SnSe2(1−x)S2x (x = 0–1) under compressive and tensile strain were investigated using density functional theory (DFT) computations. The results showed SnSe2(1−x)S2x alloys with continuously changing bandgaps from 0.8 eV for SnSe2 to 1.59 eV for SnS2. The band structure of a SnSe2(1−x)S2x monolayer can be further tuned by applied compressive and tensile strain. Moreover, tensile strain provides a direct approach to improve the catalytic activity for the hydrogen evolution reaction (HER) on the basal plane of the SnSe2(1−x)S2x monolayer. SnSeS and SnSe0.5S1.5 monolayers showed the best catalytic activity for HER at a tensile strain of 10%. This work provides a design for improved catalytic activity of the SnSe2(1-x)S2x monolayer.
Keywords: density functional theory (DFT); electronic properties; hydrogen evolution reaction; mechanical strain; SnSe2(1−x)S2x monolayer